Clinical, Laboratory, and Ultrasound Related Diagnoses of Thyroid Disorders: Using a Family Medicine Center Data to Assess Thyroiditis and Thyroid Nodules in the Eastern Province of Saudi Arabia - Malak A. Al-Shammari; Moataza M. Abdel Wahab; Nouf A. AlShamlan; Reem S. AlOmar; Abdullatif K. Althunyan; Layla M. Alghamdi; Adam Fahad Aldhawyan; Naheel A. AlAmer; Sara A. Elmaki; Omran Al Dandan (SAGE Publishing, 2022)
Introduction/Objectives: The prevalence of thyroid disorders is high in Saudi Arabia. Among the disorders, goiter and thyroiditis are the most common and have unique ultrasound (US) features, underscoring the need for US screening for thyroid pathologies. This study aimed to determine the prevalence of thyroiditis and thyroid nodules in patients attending the Family and Community Medicine Center of Imam Abdulrahman Bin Faisal University. Methods: This registry-based cross-sectional study analyzed laboratory and US data from 240 patients who attended the Family and Community Medicine Center of Imam Abdulrahman Bin Faisal University from January 2020 to December 2021. Abnormalities of the thyroid gland were categorized according to laboratory and US data. Associations between different types of thyroid pathology and clinical and laboratory findings were assessed using appropriate statistical methods. Results: The majority of participants were Saudi women. The prevalence of thyroiditis in the study population was 43%. Approximately 25% of these patients had more than 1 nodule, and fine-needle aspiration biopsy showed that most nodules were benign. Most nodules were found in clinically euthyroid patients. Thyroiditis might be associated with abnormal thyroid function. Conclusions: Thyroiditis and thyroid nodules were common in our cohort. Vitamin D deficiency, other autoimmune diseases, and a family history of thyroid disorders were associated with thyroiditis and thyroid nodules. US is useful for identifying the type of thyroid disease.